PERESEPSI GURU PAI ALUMNI FITK UIN RADEN FATAH PALEMBANG TERHADAP PRAKTIK PEMBELAJARAN DI SEKOLAH DASAR - Lailatul Aulia; Shafira Agustina Putri; Dapa Al-Dimas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the perceptions of alumni teachers from the faculty of Islamic Education and Teacher Treaning (FITK) UIN Raden Fatah Palembang regarding the implementation of Islamic religious education (PAI) in primary school. Using a qualitative phenomenological approach, data were collected trough semi-structured interviews with alumni teacher, classroom observations, and document analysis. Finding reveal three major themes : (1) a gap between university pedagogy and classroom realistis, (2) adaptive teacing strategies developed by alumni to respond to contextual constraints, and (3) institutional and infrastructural support affecting lesson delivery. The study recommends strengthening practical school-based training during undergraduate programs, on going in-service mentoring, and curriculum adjustment to better align theory and practice. The research contributes practical suggestion for teacher education program and school stakeholders to improve PAI learning quality.